Kolaborasi Perpustakaan Umum dan Masyarakat dalam Pengembangan Masyarakat - Mahdi, Reza (Perpustakaan Universitas Gadjah Mada, 2023)
Public libraries always provide benefits to the surrounding community beyond just providing books to read. How public libraries ensure that the information collections they have can be useful for the community for their survival is a problem that must be resolved. Therefore, community development is an activity that supports the role of public libraries in creating a skilled and knowledgeable community. Public libraries do not need to do it alone, but can collaborate with the community in its implementation. This study focuses on how important and the implementation of the collaboration between public library and community in community development activity. The importance of collaboration can be seen by the benefits, there are 1) accelerating changes in society; 2) generating social cohesion; 3) creating a good climate for the flow of knowledge in society, and 4) increasing community participation in public libraries. For its application it varies from the problems and potential of the existing culture. Therefore, the collaboration of public libraries with the community can grow the social capital of the public library itself.